Strategi Rekrutment Tenaga Kerja Freelance di CV Fajar Duta Kreasindo - Barkah Ibnu Romadon; Uus MD Fadli (Penerbit Yayasan Daarul Huda Kruengmane, 2023)
Travel Agency is a service business that provides organizing and coordinating services for all needs related to tourist events. Tourism is a travel activity carried out by a person or group of people by visiting certain places for recreational purposes, personal development, or studying the uniqueness of the tourist attractions visited in a temporary period. Travel Agency aims to help potential customers to determine travel and fulfill their various desires. This research uses descriptive and qualitative research methods. The descriptive method is used to present systematic and accurate facts and events regarding the nature of the population. In this study, the authors were directly involved in the field to collect data and carry out data analysis which produced information in the form of written or spoken words from the respondents and the observed behavior. The strategy for recruiting freelance workers in the field of travel agent services at CV Fajar Duta Kreasindo needs to be done carefully to get a workforce that fits the company's needs. In this discussion, we have identified several strategies that can be implemented, including building networks with related parties, creating clear job descriptions and qualifications, using online filling platforms, adopting tests and selection interviews, and verifying references and work experience.